2020
DOI: 10.3390/molecules25092050
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Chemical Synthesis and Evaluation of Anticancer Nucleoside Analogues

Abstract: Nucleoside analogues have proven to be highly successful chemotherapeutic agents in the treatment of a wide variety of cancers. Several such compounds, including gemcitabine and cytarabine, are the go-to option in first-line treatments. However, these materials do have limitations and the development of next generation compounds remains a topic of significant interest and necessity. Herein, we discuss recent advances in the chemical synthesis and biological evaluation of nucleoside analogues as potential antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 82 publications
(98 reference statements)
0
52
0
Order By: Relevance
“…In this research, our strategy was directed towards developing new fused uracil derivatives of potential anticancer activity [ 33 , 34 ]. The desired starting materials, including 6-amino-1-benzyluracil 1a [ 35 ] and 5,6-diamino-1-(2-chlorobenzyl)uracil 4 [ 36 ] were synthesized according to the literature by conventional methods.…”
Section: Resultsmentioning
confidence: 99%
“…In this research, our strategy was directed towards developing new fused uracil derivatives of potential anticancer activity [ 33 , 34 ]. The desired starting materials, including 6-amino-1-benzyluracil 1a [ 35 ] and 5,6-diamino-1-(2-chlorobenzyl)uracil 4 [ 36 ] were synthesized according to the literature by conventional methods.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been shown that warm/hot-natured herbs contain more nucleotides and their derivatives (Figures 4 and 5). Immunity, inflammation, and cancer can all be regulated by extracellular nucleosides [33][34][35]. Furthermore, based on the functional activities of the metabolites, Liang et al searched the protein targets of active compounds in the PubChem database and found that immune regulation was more related to hot-natured herbs and that cold-natured herbs possess the tendency to impact cell growth and proliferation [36].…”
Section: Discussionmentioning
confidence: 99%
“…The carbocyclic analogues of nucleosides attenuate the synthesis of DNA by acting as chain terminators after incorporating to the growing DNA chain. The prevention of the DNA chain elongation by carbocyclic analogues of nucleosides offers antineoplastic properties [35] …”
Section: Anticancer Properties Of Indane and Its Analoguesmentioning
confidence: 99%